Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/2058460120937381
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast density assessments according to BI-RADS 4th and 5th editions and experience level

Abstract: Background Breast density is an important variable that can change the sensitivity of mammography. It can be analyzed with using the 4th and 5th editions of the Breast Imaging and Reporting Data System (BI-RADS) recommendations from the American College of Radiology (ACR). Purpose To define the intra- and inter-reader agreement levels of breast density assignments performed by readers with different experience levels using two versions of BI-RADS. Material and Methods The breast density assessments of 330 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…In the fifth edition, percentage quartiles are removed with the goal to better identify women whose cancers may be masked by dense breast tissue [ 23 ]. Multiple studies have shown that BI-RADS lexicon 5th edition is associated with significant higher numbers of dense assessments compared to the fourth edition [ 53 , 54 ]. This might also explain the lower risk estimate than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the fifth edition, percentage quartiles are removed with the goal to better identify women whose cancers may be masked by dense breast tissue [ 23 ]. Multiple studies have shown that BI-RADS lexicon 5th edition is associated with significant higher numbers of dense assessments compared to the fourth edition [ 53 , 54 ]. This might also explain the lower risk estimate than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the BI‐RADS was updated in 2013, and the breast density composition scale was modified 43 . Studies have shown that the percentage of women with dense breasts when classified using the fifth edition was slightly higher than when using the fourth edition 37,44,45 . However, women who underwent mammographic screening in both 2019 to 2010 and 2011 to 2012 were included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…43 Studies have shown that the percentage of women with dense breasts when classified using the fifth edition was slightly higher than when using the fourth edition. 37,44,45 However, women who underwent mammographic screening in both 2019 to 2010 and 2011 to 2012 were included in our study. Thus, we used the BI-RADS fourth edition in our study for breast classification.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, by shifting the target from tissue percentage to parenchymal density, the new classification became more subjective, and the visual assessments of the BI-RADS categories showed a heterogeneous level of agreement between readers that varied from "slight" to "almost perfect", as reported in previously published papers [18,19]. This discrepancy persisted due to many reasons, which included differences in the study populations, the reader's level of experience, and the methods used in the study [20]. To support the analysis and to reduce the inter-reader variability, existing or new software has been upgraded to carry out an automatic assessment of breast density by analyzing mammographic images with machine-learning procedures, focusing on the distribution pattern of breast tissue rather than breast volumetric density alone.…”
Section: Introductionmentioning
confidence: 77%